Effects of different fixatives on staining patterns of four lectins in cultured microvascular endothelial cells. (26th March 2015) - Sun, Xiong; Yang, Zhongjin; Mu, Xiang; Zhang, Tao
Abstract : Fixatives have significant influence on lectin histochemistry of tissue sections; however, their roles in lectin fluorescent staining of cultured cells remain unclear. In this study, using cultured microvascular endothelial cells (MVECs) from rat intestinal mucosa, the effects of seven fixatives on the fluorescent staining patterns of four lectins were investigated. The results indicated that every fixative gave concanavalin A (Con A) and wheat germ agglutinin (WGA) strong positive staining in different patterns. When fixed with Zenker's, periodate–lysine–paraformaldehyde (PLP), 2·5% glutaraldehyde (GA), and 4% paraformaldehyde (PFA) solution, the cell membranes and cytoplasms stained, and the fluorescence in the cell edges was brighter. Rossman's solution, 95% ethanol, and acetone fixation caused cytoplasmic staining, while the fluorescence was weak and evanescent when using acetone. Dolichos biflorus agglutinin (DBA) and Ulex europaeus agglutinin I (UEA I) were stained; revealing very faint fluorescence in cytoplasms just when PLP and 2·5% GA solution were used. In conclusion, this study shows that fixatives have significant effects on the fluorescent staining of MVECs. Fixatives containing aldehydes and mercury chloride are better options for cell membrane glycans, and those containing ethanol for cytoplasmic ones. Acetone fixation is not suitable for lectin histochemistry.